Manajemen Kepemimpinan Pembelajaran Guru Paud Di Kabupaten Seluma - Bendriyanti, Rita Prima; Haryono, Mimpira; Suwarni, Suwarni; Pebriani, Ela (LPPM Universitas Dehasen Bengkulu, 2025)
Learning leadership is a crucial aspect in improving the quality of early childhood education (PAUD). However, in Seluma Regency, there are still many PAUD teachers who face limitations in implementing optimal learning leadership management. This community service activity aims to improve the capacity of PAUD teachers as learning leaders through training, workshops, and direct assistance. The method used is a participatory approach with data collection techniques in the form of observation, interviews, and questionnaires. The results of the activity showed a significant increase in teacher understanding and skills in designing, implementing, and evaluating child-based learning. Teachers began to apply a reflective, collaborative approach, and utilize the surrounding environment as a learning resource. As many as 82% of participants stated that they were more confident in leading learning, and 75% were able to identify weaknesses and make improvements. This activity also encouraged the formation of a teacher learning community that supports ongoing professionalism. Continuous support from various parties is needed so that the transformation of learning leadership in PAUD can take place consistently and have a broad impact.